Find the positive value of following expression?
1 + 1 + 1 + . . . . . ∞ 6 6 6
Here, infinity means adding 1 + 6 goes on till infinity.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You don't need to specify for the positive value. The expression is not negative because it is a positive number divided by another positive number. The negative solution you get is extraneous.
Log in to reply
I know that. I just gave an explanation of why I ignored the negative root of the quadratic , not the original question. What you told is another explanation. :)
Log in to reply
It's just that your phrasing implies that the expression has multiple values and you are picking the positive one. I think it would have been better to directly say it was extraneous.
good one !!!!!!!!!!1
Let x = 1 + 1 + . . . ∞ 6 6 . Then:
x = 1 + x 6
x 2 + x − 6 = 0
( x + 3 ) ( x − 2 ) = 0
Since only the positive value is required, x = 2
x = 6/1+x ---> x(x+1)= 6 ---> x^2 + x - 6 = 0 (x-2)(x+3) = 6 ---> x = 2 or -3(impossible). So, x is 2. Answer ; 2
Let 1 + 1 + 1 + 1 + . . . 6 6 6 6 = x . Therefore, we can dramatically simplify this as 1 + x 6 = x . This leads to x 2 + x = 6 , or x 2 + x − 6 = 0 . Factoring gives us ( x + 3 ) ( x − 2 ) = 0 , so the positive value of the expression is 2 .
Let, Y= 6/ 1+6/(1+6/1+..infinity )
so, we can write Y =6/(1+6/Y) as Y given ,
solving the quadratic equation we will get
( Y+3) ( Y -2) =0 .
as we have to take positive number Y = 2
The key to this question lies inside the expression itself. It we let the expression equal x :
x = 1 + 1 + 1 + … 6 6 6
Then the value (that I marked with a box) is ALSO equal to x, since it's the same thing!
x = 1 + 1 + 1 + … 6 6 6
So instead of that box, let's rewrite it as x. The reason this is important is that we now reduced the fraction that goes on until infinity, to a simple equation that we know how to solve!
x = 1 + x 6
Let's multiply both sides by 1 + x :
x ( 1 + x ) = 6
Now we open the parenthesis:
x + x 2 = 6
And we have a quadratic equation!
x 2 + x − 6 = 0
( x − 2 ) ( x + 3 ) = 0
The solutions are therefore x = 2 OR x = − 3 ...
Oh wait, we have two solutions?! Remember that the question says:
Find the positive value
So the only answer left is x = 2 .
1 + 6 / 1 . . . 6 = x, → 1 + x 6 = x
x 2 + x − 6 = ( x + 3 ) ( x − 2 ) = 0
x = − 3 or x = 2 the question asks the positive value, so x = 2
Let f ( x ) = 1 + x 6 and consider the sequence x , f ( x ) , f 2 ( x ) , ⋯ . Suppose the sequence converges to z for some initial x and f is continuous there, then continuity preserves limits, and we know that f ( z ) = z is a stable fixed point. Therefore, the answer comes from the solution of the quadratic equation z = 1 + z 6 , which is finitely equivalent to the quadratic z 2 + z − 6 = 0 . The positive root of this is 2 , which is our answer.
Problem Loading...
Note Loading...
Set Loading...
Let... x = 1 + 1 + 1 + 1 + … ∞ 6 6 6 6
⟹ x = 1 + x 6
⟹ x ( x + 1 ) = 6 = 2 × 3 = 2 × ( 2 + 1 )
∴ x = 2
Note : The last equation is quadratic and has two solutions (the other is − 3 ), but the question asks for positive value so I didn't go that way... :3